Development Of Biology E-Modules Based On Islamic, Science, Environment, Technology, And Society Using Exelearning On Bacterial Material - Maharani Conilie; Bayu Sandika; Aushia Tanzih Al Haq (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
Online learning during the COVID-19 pandemic is a choice so that learning can continue. However, in its implementation, various obstacles were found. These obstacles are caused by poor internet networks, limited internet quotas, and the availability of teaching materials that do not support the online learning process. Therefore the objectives of this study are to describe: 1) The validity of the biology e-module, 2) The practicality of the biology e-module, and 3) Students’ responses to the biology e-module based on I-SETS using eXeLearning on bacterial material. The method used in this study is the research and development method with the ADDIE model. The result shows that: 1) The average validity results of biology e-modules, include the material validity of 94,5% (very valid) and the media validity of 95% (very valid), 2) The practicality of the biology e-module was obtained at 94% (very practical), and 3) The average student’s responses to the biology e-module was obtained at 85% (very good). So, it can be concluded that the biology e-module that has been successfully developed can be used in online biology learning. Pembelajaran daring selama pandemi COVID-19 menjadi alternatif pilihan agar pembelajaran tetap dapat berlangsung. Akan tetapi dalam pelaksanaannya ditemukan berbagai kendala. Kendala-kendala tersebut disebabkan oleh jaringan internet yang buruk, kuota internet yang terbatas, dan ketersediaan bahan ajar yang kurang mendukung proses pembelajaran daring. Oleh karena itu, tujuan penelitian ini untuk mendeskripsikan: 1) Validitas e-modul biologi, 2) Praktikalitas e-modul biologi, dan 3) Respons siswa terhadap e-modul biologi berbasis I-SETS menggunakan eXeLearning pada materi bakteri. Metode yang digunakan dalam studi ini adalah metode penelitian dan pengembangan dengan model ADDIE. Hasil studi menunjukkan bahwa: 1) Rata-rata validitas e-modul biologi, meliputi validitas materi sebesar 94,5% (sangat valid) dan validitas media sebesar 95% (sangat valid), 2) Praktikalitas e-modul biologi sebesar 94% (sangat praktis), dan 3) Rata-rata respons siswa terhadap e-modul biologi sebesar 85% (sangat baik). Maka dapat disimpulkan e-modul biologi yang berhasil dikembangkan dapat digunakan dalam pembelajaran biologi secara daring.